Correlation of stability and complications measurements in traumatic hip dislocation cases associated with posterior wall acetabular fracture (Annals of Medical Research, 2021)
None
Keywords: Acetabular Fracture; Hip Dislocation; Posterior Acetabular Arc Angle; Kocher Langenbeck Approach.